Plantão psicoeducativo para jovens em uma periferia da cidade de São Paulo: uma experiência provocadora de uma reflexão sobre práticas educativas - Sanchez, Regina Suini (2006)
The present study had the objective to understand how the Psycho Educational Duty Service could offer an opportunity of reflection for youth that live in the outskirts of the city of Sao Paulo. It was considered that an opportunity for reflecting about one s own life creates an educational environment, once it aims to invite youth to their responsibility before themselves and the world. Hanna Arendt s thoughts directed the insight towards the educational issue. It was an interference research done in the context of Psycho Educational Duty Service based on the existential phenomenological reference Two months after the Youth Duty Services and listening to four adolescents, two stories were chosen that showed the educational character of this practice. The issues brought by the Youth were referred to existential choices and their relationship with the world and with the future. The Duty Service sowed itself as an opportunity for those young people to be involved with their future looking for new exits, seen at the beginning inescapable, through dialog and reflection. Non violence was perceived and analyzed as derived of the reflection possibility. This research aimed contributing to the development of educational practices directed to youth, based on the report of dialogues that took place during the Duty Service and by the reflection, about the educational issue indicated above initiated by this procedure